Heritage and Resilience: Sustainable Recovery of Historic Syrian Cities - Emad Noaime; Mohammed Mashary Alnaim (Buildings, 2025)
This study investigates the challenges and opportunities of balancing cultural preservation, tourism investment, and community resilience in historic Syrian cities during the post-war recovery period. The Syrian conflict has imposed considerable harm upon the nation’s cultural heritage, encompassing UNESCO World Heritage sites, thereby interrupting not only the urban infrastructure but also local economies and social networks. Utilizing a comprehensive methodology that includes a literature review, stakeholder interviews, and local surveys, this research investigates the potential for aligning cultural preservation with tourism investment to promote sustainable economic revitalization while simultaneously enhancing social cohesion and community resilience. The results underscore the significance of inclusive governance, participatory planning, and capacity enhancement to guarantee that post-conflict urban redevelopment fosters enduring environmental, social, and cultural sustainability. By framing the Syrian case within the broader context of global urban sustainability and resilience discourse, the study offers valuable insights for policymakers, urban planners, and heritage managers working in post-conflict or post-disaster environments worldwide. In the end, the study highlights that the revitalization of historic cities transcends being a simple technical or economic endeavor; it is a complex process of re-establishing identity, strengthening communities, and fostering sustainable, resilient urban futures.